A review on the use of lichens as a biomonitoring tool for environmental radioactivity. (March 2022) - Anderson, J.; Lévesque, N.; Caron, F.; Beckett, P.; Spiers, G.A.
Abstract: Lichens have been widely used as a biomonitoring tool to record the distribution and concentration of airborne radioactivity and pollutants such as metals. There are limitations, however: although pollutants can be preserved in lichen tissues for long periods of time, not all radioactive and inert elements behave similarly. The chemical species of elements at the source, once captured, and the mode of storage within lichens play a role in this biomonitoring tool. Lichens are a symbiotic association of an algal or cyanobacterial partner (photobiont) with a fungal host (mycobiont). Lichens grow independently of the host substrates, including rocks, soils, trees and human-made structures. Lacking a root system, lichen nutrient or contaminant uptake is mostly through direct atmospheric inputs, mainly as wet and dry deposition. As lichens grow in a large variety of environments and are resilient in harsh climates, they are adapted to capture and retain nutrients from airborne sources. The context of this review partially relates to future deployment of small modular reactors (SMRs) and mining in remote areas of Canada. SMRs have been identified as a future source of energy (electricity and heat) for remote off-grid mines, potentially replacing diesel fuel generation facilities. For licensing purposes, SMR deployment and mine development requires capabilities to monitor background contaminants (natural radioactivity and metals) before, during and after deployment, including for decommissioning and removal. Key aspects reviewed herein include: (1) how lichens have been used in the past to monitor radioactivity; (2) radiocontaminants capture and storage in lichens; (3) longevity of radiocontaminant storage in lichen tissues; and (4) limitations of lichens use for monitoring radiocontaminants and selected metals. Highlights: Lichens are potentially useful biomonitors for radioactive contamination. Radiocontaminant uptake by lichens is well documented for Cs. Factors affecting the half-life of radiocontaminants in lichens was reviewed. An updated model for radiocontaminant uptake is proposed for lichens.